Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Collective and harmonized high throughput barcoding of insular arthropod biodiversity: Toward a Genomic Observatories Network for islands - Brent C. Emerson; Paulo A. V. Borges; Pedro Cardoso; Peter Convey; Jeremy R. deWaard; Evan P. Economo; Rosemary G. Gillespie; Susan Kennedy; Henrik Krehenwinkel; Rudolf Meier; George K. Roderick; Dominique Strasberg; et al. (Molecular Ecology, 2023)
Current understanding of ecological and evolutionary processes underlying island biodiversity is heavily shaped by empirical data from plants and birds, although arthropods comprise the overwhelming majority of known animal species, and as such can provide key insights into processes governing biodiversity. Novel high throughput sequencing (HTS) approaches are now emerging as powerful tools to overcome limitations in the availability of arthropod biodiversity data, and hence provide insights into these processes. Here, we explored how these tools might be most effectively exploited for comprehensive and comparable inventory and monitoring of insular arthropod biodiversity. We first reviewed the strengths, limitations and potential synergies among existing approaches of high throughput barcode sequencing. We considered how this could be complemented with deep learning approaches applied to image analysis to study arthropod biodiversity. We then explored how these approaches could be implemented within the framework of an island Genomic Observatories Network (iGON) for the advancement of fundamental and applied understanding of island biodiversity. To this end, we identified seven island biology themes at the interface of ecology, evolution and conservation biology, within which collective and harmonized efforts in HTS arthropod inventory could yield significant advances in island biodiversity research.

Richness and resilience in the Pacific: DNA metabarcoding enables parallelized evaluation of biogeographic patterns - Susan Kennedy; Jerilyn Calaor; Yazmín Zurápiti; Julian Hans; Masashi Yoshimura; Juanita Choo; Jeremy C. Andersen; Jackson Callaghan; George K. Roderick; Henrik Krehenwinkel; Haldre Rogers; Rosemary G. Gillespie; et al. (Molecular Ecology, 2023)
Islands make up a large proportion of Earth's biodiversity, yet are also some of the most sensitive systems to environmental perturbation. Biogeographic theory predicts that geologic age, area, and isolation typically drive islands' diversity patterns, and thus potentially impact non‐native spread and community homogenization across island systems. One limitation in testing such predictions has been the difficulty of performing comprehensive inventories of island biotas and distinguishing native from introduced taxa. Here, we use DNA metabarcoding and statistical modelling as a high throughput method to survey community‐wide arthropod richness, the proportion of native and non‐native species, and the incursion of non‐natives into primary habitats on three archipelagos in the Pacific – the Ryukyus, the Marianas and Hawaii – which vary in age, isolation and area. Diversity patterns largely match expectations based on island biogeography theory, with the oldest and most geographically connected archipelago, the Ryukyus, showing the highest taxonomic richness and lowest proportion of introduced species. Moreover, we find evidence that forest habitats are more resilient to incursions of non‐natives in the Ryukyus than in the less taxonomically rich archipelagos. Surprisingly, we do not find evidence for biotic homogenization across these three archipelagos: the assemblage of non‐native species on each island is highly distinct. Our study demonstrates the potential of DNA metabarcoding to facilitate rapid estimation of biogeographic patterns, the spread of non‐native species, and the resilience of ecosystems.

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Ancient biogeography of generalist predators on remote oceanic islands - R. G. Gillespie; M. S. Brewer; G. K. Roderick (Journal of Biogeography, 2017)
Aim Remote islands are known for providing spectacular examples of adaptive radiation, with ecological divergence across a lineage giving rise to multiple species, each specialized for a particular niche. These isolated environments also provide some of the best examples of recent colonization, often human‐mediated, with a single generalist taxon distributed over vast regions. Highlighted by this dichotomy is a tendency of taxa to become more specialized over time. The current study focuses on two spider taxa (family Uloboridae) each occupying a broad range of habitats: Tangaroa tahitiensis in the Austral and Society islands of French Polynesia and Daramulunia gibbosa in Fiji. We ask whether the generalist tendency of each is associated with recent colonization of widespread species or, rather, maintained over extended evolutionary time. Location South Pacific: Fiji (18° S, 175° E), Society (18° S, 150° W), and Austral (23° S, 150° W) archipelagoes. Methods Mitochondrial COI and nuclear 18S rDNA were sequenced and analysed using maximum likelihood ( RA x ML ) and Bayesian approaches with concurrent divergence dating calibrated with a general arthropod molecular clock. Ancestral ranges were reconstructed independently for French Polynesia and Fiji ( RASP ). Results While both T. tahitiensis and D. gibbosa occur broadly from sea‐level to cloud forest, each has a separate and ancient origin within their respective archipelagoes, the pattern of colonization matching the geographical arrangement of the islands. Main conclusions Populations of two spider species, T. tahitiensis in the Australs and Societies and D. gibbosa in Fiji, are extreme generalists with broad physiological tolerances throughout their respective ranges. Yet, every population displays single island endemism and deep genetic divergences between islands indicating a long history on individual landmasses, a finding that contradicts the tendency for organisms to show increasing specialization associated with endemism.

Stepping‐stones across space and time: repeated radiation of Pacific flightless broad‐nosed weevils (Coleoptera: Curculionidae: Entiminae: Rhyncogonus ) - Elin M. Claridge; Rosemary G. Gillespie; Michael S. Brewer; George K. Roderick (Journal of Biogeography, 2017)
Aim We examine spatial and temporal patterns of diversification among flightless weevils in the genus Rhyncogonus (Curculionidae: Entiminae), with respect to their passive mode of dispersal by rafting or upon birds and the geological context of Pacific island archipelagos. Location Archipelagos and islands of the Pacific Ocean, especially the South Pacific and Hawaii. Methods Nuclear and mitochondrial DNA sequence data were used in Bayesian and maximum likelihood analyses to generate a phylogenetic hypothesis for all available species within the genus Rhyncogonus , plus representatives of other tribes in the subfamily Entiminae. Bayesian inference with molecular and geological calibration points was also used to estimate the age of major lineages of Rhyncogonus and infer the history of colonization. Results The genus Rhyncogonus has colonized all major archipelagos in the central Pacific, with multiple species occurring within nearly all archipelagos. The common ancestors of the genus were present in the central Pacific at least 15 Ma, probably first inhabiting islands now under water. Subsequent colonization and diversification across Oceania shows a pattern that is remarkably consistent with the geology of the region: the weevils, which likely disperse either by rafting on vegetation or on migratory birds, reached each island not long after its appearance. Main conclusions Though flightless, weevils in the genus Rhyncogonus have been remarkably effective at colonizing islands of the Pacific and appear to have colonized more remote islands via a series of less remote archipelagos. Although such a process of dispersal has been predicted, this study provides the first clear demonstration of the role of stepping‐stones in the diversification of a lineage with passive dispersal.

Community assembly on isolated islands: macroecology meets evolution - A. J. Rominger; K. R. Goodman; J. Y. Lim; E. E. Armstrong; L. E. Becking; G. M Bennett; M. S. Brewer; D. D. Cotoras; C. P. Ewing; J. Harte; N. D. Martinez; P. M. O'Grady; et al. (Global Ecology and Biogeography, 2016)
Aim Understanding how ecological and evolutionary processes together determine patterns of biodiversity remains a central aim in biology. Guided by ecological theory, we use data from multiple arthropod lineages across the Hawaiian archipelago to explore the interplay between ecological (population dynamics, dispersal, trophic interactions) and evolutionary (genetic structuring, adaptation, speciation, extinction) processes. Our goal is to show how communities develop from the dynamic feedbacks that operate at different temporal and spatial scales. Location The Hawaiian islands (19–22° N , 155–160° W ). Methods We synthesize genetic data from selected arthropods across the Hawaiian archipelago to determine the relative role of dispersal and in situ differentiation across the island chronosequence. From four sites on three high islands with geological ages ranging from Results From the perspective of the island chronosequence we show that species at lower trophic levels develop population genetic structure at smaller temporal and spatial scales than species at higher trophic levels. Network nestedness decreases while modularity increases with habitat age. Single‐island endemics exhibit more specialization than broadly distributed species, but both show the least specialization in communities on middle‐aged substrates. Plant–herbivore networks also show the least deviation from theoretical predictions in middle‐aged communities. Main conclusions The application of ecological theory to island chronosequences can illuminate feedbacks between ecological and evolutionary processes in community assembly. We show how patterns of population genetic structure, decreasing network nestedness, increasing network modularity and increased specialization shift from early assembly driven by immigration, to in situ diversification after > 1 Myr. Herbivore–plant communities only transiently achieve statistical steady state during assembly, presumably due to incomplete assembly from dispersal in the early stages, and the increasing influence of island ontogeny on older islands.

H alomonas sulfidaeris ‐dominated microbial community inhabits a 1.8 km‐deep subsurface C ambrian S andstone reservoir - Yiran Dong; Charu Gupta Kumar; Nicholas Chia; Pan‐Jun Kim; Philip A. Miller; Nathan D. Price; Isaac K. O. Cann; Theodore M. Flynn; Robert A. Sanford; Ivan G. Krapac; Randall A. Locke; Pei‐Ying Hong; et al. (Environmental Microbiology, 2014)
Summary A low‐diversity microbial community, dominated by the γ ‐proteobacterium H alomonas sulfidaeris , was detected in samples of warm saline formation porewater collected from the C ambrian Mt. S imon S andstone in the I llinois B asin of the N orth A merican M idcontinent (1.8 km/5872 ft burial depth, 50° C , pH 8, 181 bars pressure). These highly porous and permeable quartz arenite sandstones are directly analogous to reservoirs around the world targeted for large‐scale hydrocarbon extraction, as well as subsurface gas and carbon storage. A new downhole low‐contamination subsurface sampling probe was used to collect in situ formation water samples for microbial environmental metagenomic analyses. Multiple lines of evidence suggest that this H . sulfidaeris ‐dominated subsurface microbial community is indigenous and not derived from drilling mud microbial contamination. Data to support this includes V 1‐ V 3 pyrosequencing of formation water and drilling mud, as well as comparison with previously published microbial analyses of drilling muds in other sites. Metabolic pathway reconstruction, constrained by the geology, geochemistry and present‐day environmental conditions of the Mt . S imon S andstone, implies that H . sulfidaeris ‐dominated subsurface microbial community may utilize iron and nitrogen metabolisms and extensively recycle indigenous nutrients and substrates. The presence of aromatic compound metabolic pathways suggests this microbial community can readily adapt to and survive subsurface hydrocarbon migration.

Species Differentiation on a Dynamic Landscape: Shifts in Metapopulation Genetic Structure Using the Chronology of the Hawaiian Archipelago - George K. Roderick; Peter J. P. Croucher; Amy G. Vandergast; Rosemary G. Gillespie (Evolutionary Biology, 2012)

Biodiversity dynamics in isolated island communities: interaction between natural and human‐mediated processes - ROSEMARY G. GILLESPIE; ELIN M. CLARIDGE; GEORGE K. RODERICK (Molecular Ecology, 2008)
The flora and fauna of oceanic islands have inspired research since the early scientific explorations. Islands can be considered ‘nature's test tubes’— simple systems with multiple replicates. Our research has used the simplicity of island systems to understand ecological community dynamics and to compare the properties of island communities with those in more complex mainland systems. Here, we present three topics: (i) current patterns of biodiversity on isolated islands of the Pacific; (ii) current patterns of disturbance and invasion on islands; and (iii) future trajectories inferred from these patterns. We examine features of islands (in particular, topography and isolation) that have allowed for given levels and distribution of endemicity. The extent to which island communities are impacted by, resist or accommodate disturbance and/or invasions by nonindigenous species appears to be dictated to a large extent by properties of the native communities and how these communities were originally assembled. Accordingly, patterns of disturbance and invasion are very different for high (montane) islands that are extremely isolated compared to those that are nearer to a source of natural migrants. As with all biotas, those on islands are dynamic entities. However, the unique aspect of islands is their isolation, and extreme isolation has largely been lost over the course of the last few centuries due to the development of transportation routes. We argue that such a modified dynamic will affect the future of the biota and the processes that gave rise to the biota. Specifically for isolated habitats, ecological processes will become increasingly more likely to generate biodiversity than evolutionary processes which have been relatively more important in the past. In the short term, island biotas and other similar biotas that occur in montane habitats may fare well as species are often abundant locally in the habitat to which they are indigenous, and may demonstrate considerable resistance and resilience to invasion. However, island biotas — and other biotas that show high local endemism — will likely not fare well in the face of prolonged disturbance. The biotas in these areas generally display a relatively low dispersal capacity; therefore, under conditions of long‐term habitat modification, isolated biotas are likely to be swamped by non‐natives, which — simply because of random processes and higher propagule pressure — will move more readily into available habitats. Thus, despite the importance of incorporating the evolutionary process into conservation efforts, we must also be careful to evaluate the likely form that the processes will take when the context (specifically, extent of isolation) has been highly modified.

Influence of volcanic activity on the population genetic structure of Hawaiian Tetragnatha spiders: fragmentation, rapid population growth and the potential for accelerated evolution - Amy G. Vandergast; Rosemary G. Gillespie; George K. Roderick (Molecular Ecology, 2004)
Volcanic activity on the island of Hawaii results in a cyclical pattern of habitat destruction and fragmentation by lava, followed by habitat regeneration on newly formed substrates. While this pattern has been hypothesized to promote the diversification of Hawaiian lineages, there have been few attempts to link geological processes to measurable changes in population structure. We investigated the genetic structure of three species of Hawaiian spiders in forests fragmented by a 150‐year‐old lava flow on Mauna Loa Volcano, island of Hawaii: Tetragnatha quasimodo (forest and lava flow generalist), T. anuenue and T. brevignatha (forest specialists). To estimate fragmentation effects on population subdivision in each species, we examined variation in mitochondrial and nuclear genomes (DNA sequences and allozymes, respectively). Population subdivision was higher for forest specialists than for the generalist in fragments separated by lava. Patterns of mtDNA sequence evolution also revealed that forest specialists have undergone rapid expansion, while the generalist has experienced more gradual population growth. Results confirm that patterns of neutral genetic variation reflect patterns of volcanic activity in some Tetragnatha species. Our study further suggests that population subdivision and expansion can occur across small spatial and temporal scales, which may facilitate the rapid spread of new character states, leading to speciation as hypothesized by H. L. Carson 30 years ago.

Growth and nutritional trials on transgenic Nile tilapia containing an exogenous fish growth hormone gene - M. A. Rahman; A. Ronyai; B. Z. Engidaw; K. Jauncey; G‐L. Hwang; A. Smith; E. Roderick; D. Penman; L. Varadi; N. Maclean (Journal of Fish Biology, 2001)
In a long‐term growth trial, transgenic tilapia Oreochromis niloticus L. showed a 2·5‐fold increase in growth compared with non‐transgenic siblings. At 7 months, mean mass of transgenic tilapia was 653 g compared with 260 g for non‐transgenic siblings. A significant increase ( P >0·01) in head: total length ratio, viscera‐somatic index and hepato‐somatic index was observed in transgenic fish. Female gonado‐somatic index ( I G) was found to be lower in transgenics than non‐transgenic siblings in both mixed and separate culture conditions. Transgenic male I G values were found to be higher in mixed culture and lower in separate culture than that of their non‐transgenic siblings. Food conversion efficiency was more than 20% greater in the transgenic fish. In a second shorter‐term growth performance trial, the transgenic fish grew to about four times the size of their non‐transgenic siblings. A digestibility trial suggested that transgenic tilapia were more efficient utilizers of protein, dry matter and energy. Apparent digestibility of protein and apparent energy digestibility were higher in the transgenic fish.

Invasion genetics of the Mediterranean fruit fly: variation in multiple nuclear introns - F. X. VILLABLANCA; G. K. RODERICK; S. R. PALUMBI (Molecular Ecology, 1998)
Biological invasions generally start from low initial population sizes, leading to reduced genetic variation in nuclear and especially mitochondrial DNA. Consequently, genetic approaches for the study of invasion history and population structure are difficult. An extreme example is the Mediterranean fruit fly, Ceratitis capitata (Medfly), for which successive invasions during this century have resulted in a loss of 60% of ancestral genetic variation in isozymes and 75% of variation in mitochondrial DNA. Using Medflies as an example, we present a new approach to invasion genetics that measures DNA sequence variation within introns from multiple nuclear loci. These loci are so variable that even relatively recently founded Medfly populations within California and Hawaii retain ample genetic diversity. Invading populations have only lost 35% of the ancestral genetic variation. Intron variation will allow high‐resolution genetic characterization of invading populations in both natural and managed systems, although non‐equilibrium methods of analysis may be necessary if the genetic diversity represents sorting ancestral polymorphism.

Speciation and phylogeography of Hawaiian terrestrial arthropods - G. K. RODERICK; R. G. GILLESPIE (Molecular Ecology, 1998)
The Hawaiian archipelago is arguably the world’s finest natural laboratory for the study of evolution and patterns of speciation. Arthropods comprise over 75% of the endemic biota of the Hawaiian Islands and a large proportion belongs to species radiations. We classify patterns of speciation within Hawaiian arthropod lineages into three categories: (i) single representatives of a lineage throughout the islands; (ii) species radiations with either (a) single endemic species on different volcanoes or islands, or (b) multiple species on each volcano or island; and (iii) single widespread species within a radiation of species that exhibits local endemism. A common pattern of phylogeography is that of repeated colonization of new island groups, such that lineages progress down the island chain, with the most ancestral groups (populations or species) on the oldest islands. While great dispersal ability and its subsequent loss are features of many of these taxa, there are a number of mechanisms that underlie diversification. These mechanisms may be genetic, including repeated founder events, hybridization, and sexual selection, or ecological, including shifts in habitat and/or host affiliation. The majority of studies reviewed suggest that natural selection is a primary force of change during the initial diversification of taxa.

Intraspecific mitochondrial DNA variation in the Colorado potato beetle,Leptinotarsa decemlineata (Coleoptera: Chrysomelidae) - A. M. L. Azeredo-Espin; R. F. W. Schroder; G. K. Roderick; W. S. Sheppard (Biochemical Genetics, 1996)

Intraspecific mitochondrial DNA variation in the Colorado potato beetle,Leptinotarsa decemlineata (Coleoptera: Chrysomelidae) - A. M. L. Azeredo-Espin; R. F. W. Schroder; G. K. Roderick; W. S. Sheppard (Biochemical Genetics, 1996)